Inoculation of common beans with Xanthomonas campestris pv. phaseoli under field conditions - Faria, Josias Corrêa de; Melo, Paulo Eduardo de (Pesquisa Agropecuaria Brasileira, 2014)
Utilization of sand blast injury for inoculation of common beans (Phaseolus vulgaris L.) with Xanthomonas campestris pv.phaseoli under field conditions was shown to be highly satisfactory. Twenty-eight to sixty-eight per cent of the total of leaves analised with common blight were obtained, compared to 8% to 16% of natural incidence. The final disease incidence and severity obtained were low and not correlated to yield. There was no difference among cultivars on the rate of disease progress, except for 'Carioca' with a lower rate than “Rio Tibagi”.
Keywords: common blight; bacterial blight; dry beans; sand blast